Update on Phytochemical and Biological Studies on Rocaglate Derivatives from Aglaia Species - Agarwal, Garima; Chang, Long-Sheng; Soejarto, Djaja Doel; Kinghorn, A. Douglas (Planta Medica, 2021)
With about 120 species, Aglaia is one of the largest genera of the plant family Meliaceae (the mahogany plants). It is native to the tropical rainforests of the Indo-Australian region, ranging from India and Sri Lanka eastward to Polynesia and Micronesia. Various Aglaia species have been investigated since the 1960s for their phytochemical constituents and biological properties, with the cyclopenta[b]benzofurans (rocaglates or flavaglines) being of particular interest. Phytochemists, medicinal chemists, and biologists have conducted extensive research in establishing these secondary metabolites as potential lead compounds with antineoplastic and antiviral effects, among others. The varied biological properties of rocaglates can be attributed to their unusual structures and their ability to act as inhibitors of the eukaryotic translation initiation factor 4A (eIF4A), affecting protein translation. The present review provides an update on the recently reported phytochemical constituents of Aglaia species, focusing on rocaglate derivatives. Furthermore, laboratory work performed on investigating the biological activities of these chemical constituents is also covered.
Keywords: Aglaia; Meliaceae; natural products; rocaglates; flavaglines; rocaglamide; silvestrol; biological effects; antineoplastic activity; antiviral activity; protein translation inhibition